Predictors of Healing Ligament Size and Magnetic Resonance Signal Intensity at 6 Months After Bridge-Enhanced Anterior Cruciate Ligament Repair. Issue 6 (May 2019) - Murray, Martha M.; Kiapour, Ata M.; Kalish, Leslie A.; Ecklund, Kirsten; Freiberger, Christina; Henderson, Rachael; Kramer, Dennis; Micheli, Lyle; Yen, Yi-Meng; Fleming, Braden C.
Background: Primary repair of the anterior cruciate ligament (ACL) augmented with a tissue engineered scaffold to facilitate ligament healing is a technique under development for patients with ACL injuries. The size (the amount of tissue) and signal intensity (the quality of tissue) of the healing ligament as visualized on magnetic resonance imaging (MRI) have been shown to be related to its strength in large animal models. Hypothesis: Both modifiable and nonmodifiable risk factors could influence the size and signal intensity of the repaired ligament in patients at 6 months after surgery. Study Design: Case series; Level of evidence, 4. Methods: 62 patients (mean age, 19.4 years; range, 14-35 years) underwent MRI of the knee 6 months after ACL repair augmented with an extracellular matrix scaffold. The signal intensity (normalized to cortical bone) and average cross-sectional area of the healing ligament were measured from the MRI stack obtained by use of a gradient echo sequence. Associations between these 2 measures and patient characteristics, which included demographic, clinical, and anatomic features, were determined by use of multivariable regression analysis. Results: A larger cross-sectional area of the repaired ligament at 6 months was associated with male sex, older age, and the performance of a larger notchplasty ( P < .05 for all associations). A lower signal intensity at 6 months, indicating greater similarity to normal ligament, was associated with a smaller tibial slope and greater side-to-side difference in quadriceps strength 3 months after surgery. Other factors, including preoperative body mass index, mechanism of injury, tibial stump length, and Marx activity score, were not significantly associated with either MRI parameter at 6 months. Conclusion: Modifiable factors, including surgical notchplasty and slower recovery of quadriceps strength at 3 months, were associated with a larger cross-sectional area and improved signal intensity of the healing ACL after bridge-enhanced ACL repair in this preliminary study. Further studies to determine the optimal size of the notchplasty and the most effective postoperative rehabilitation strategy after ACL repair augmented by a scaffold are justified. Registration: NCT02664545 (ClinicalTrials.gov identifier).